Optimal Primary Prophylaxis for Febrile Neutropenia During Neoadjuvant Cisplatin and 5‐Fluorouracil Plus Docetaxel for Esophageal Cancer: A Retrospective Cohort Study - Ryosuke Kumanishi; Hiroya Taniguchi; Taiko Nakazawa; Takatsugu Ogata; Yuki Matsubara; Hiroyuki Kodama; Akinobu Nakata; Kazunori Honda; Toshiki Masuishi; Yukiya Narita; Shigenori Kadowaki; Masashi Ando; et al. (Cancer Medicine, 2025)
ABSTRACT Background Neoadjuvant chemotherapy (NAC) with docetaxel, cisplatin, and 5‐fluorouracil (5‐FU) (DCF) is the standard treatment for locally advanced esophageal cancer (LAEC). DCF is associated with a high risk of febrile neutropenia (FN), but the optimal primary prophylaxis remains unclear. The present study aimed to assess risk factors for FN and efficacy of primary prophylaxis using granulocyte colony‐stimulating factor (G‐CSF) and antibiotics in LAEC patients treated with DCF. Methods Patients with LAEC who received DCF as NAC between January 2016 and June 2022 at Aichi Cancer Center Hospital were retrospectively analyzed. DCF consisted of docetaxel 70 mg/m2 on day 1, cisplatin 70 mg/m2 on day 1, and 5‐FU 750 mg/m2 by continuous infusion over 5 days. The patients were divided into Cohort A [no G‐CSF], B1 (G‐CSF after day 6), and B2 (G‐CSFon day 3–4). The efficacy of primary prophylaxis with G‐CSF and antibiotics during the first cycle was evaluated. The potential FN risk factors were evaluated using univariate and multivariate analyses. Results Among the 156 patients with esophageal cancer who received DCF as NAC, 41 (26%) patients developed FN during the first cycle. Multivariate analysis revealed that prophylactic antibiotics (17% vs. 40%; adjusted OR, 0.34; 95% confidence interval [CI], 0.16–0.73; p = 0.006) and G‐CSF (6% vs. 35%; adjusted OR, 0.14; 95% CI, 0.04–0.47; p = 0.002) were associated with lower FN incidence. The grade 3/4 neutropenia rates were 84%, 43%, and 13% in cohorts A, B1, and B2, respectively. FN incidence was 35%, 13%, and 0% in the respective cohorts. Treatment‐related death occurred in 2% of patients, none of whom received G‐CSF prophylaxis. Conclusions Prophylactic G‐CSF and antibiotics reduce the risk of FN in patients with LAEC treated with DCF. Early timing of G‐CSF administration showed a potential trend toward reduced FN risk and may offer additional benefits; however, these findings must be validated.